Does ownership structure matter in explaining derivatives’ use policy in French listed firms - Boubaker, S.; Salma, M.; Shaikh, Junaid (Inderscience Enterprise Ltd, UK, 2010)
The purpose of this study is to investigate the effect of ownership structure on derivatives' use policy. Using data for 262 French non-financial listed firms, the results show that the two decisions of whether to use derivatives or not and the extent of derivatives use are not affected by the same variables. CEO ownership has a negative effect on the decision to use derivatives, whereas CEO tenure length influences negatively the extent of derivative use. CEO age impacts positively both decisions, whereas firms that grant stock options to their CEOs do not rely too much on derivatives. However, the presence of outside blockholders seems not to affect the firms' hedging policy.